Performance Evaluation of Polygonal and Cylindrical Ball Mills Using Discrete Element Method - Mathew Ndeto Kyalo; James Kuria Kimotho; Hiram Muriithi Ndiritu (Engineering Reports)
ABSTRACT Ball mills are frequently utilized in the chemical and mineral processing industries to reduce the size of particles. In mineral processing, cylindrical rotating mills with wear‐resistant materials are used at various operation scales. Polygon‐shaped rotating mills are used in artisanal and small‐scale mining due to technological and economic reasons. It is imperative to thoroughly evaluate polygon‐shaped mills to inform decisions regarding their improvement or replacement based on technological data. Even a minor enhancement in grinding efficiency and mill durability can yield substantial economic and environmental advantages. In this study, the performance of polygonal‐shaped mills was evaluated and compared with cylindrical profiles, taking into account power draw, collision energy dissipation, relative wear, and operational stability. The effect of installing lifters in the mills was also assessed. Simulations using the discrete element method (DEM) were carried out to describe the mechanical behavior of grinding media and its interaction with the mill walls. Notably, polygonal‐shaped mills without lifters facilitated interparticle interaction with limited centrifuging of particles compared to cylindrical mills without lifters. The installation of lifters in polygonal mills increased interparticle collisions and reduced power draw and wear rate. Cylindrical mills with lifters had high interparticle collisions similar to polygonal profiles but with much lower wear rate and high operational stability.